Family study of inherited syndrome with multiple congenital deformities: symphalangism, carpal and tarsal fusion, brachydactyly, craniosynostosis, strabismus, hip osteochondritis. Issue 5 (October 1976) - Ventruto, V; Di Girlamo, R; Festa, B; Romano, A; Sebastio, G; Sebastio, L
Abstract : A syndrome of brachydactyly (absence of some middle or distal phalanges), aplastic or hypoplastic nails, symphalangism (ankylois of proximal interphalangeal joints), synostosis of some carpal and tarsal bones, craniosynostosis, and dysplastic hip joints is reported in five members of an Italian family. It may represent a previously undescribed autosomal dominant trait.